Spatial Analysis of Vegetation Density in Langsa City Using NDVI Index - Unsha, Fuji Attariq; Rasnovi, Saida; Dahlan (Al-Kauniyah: Jurnal Biologi, 2026)
This study aims to analyze the distribution of vegetation density in Langsa City using the Normalized Difference Vegetation Index (NDVI). The research was conducted from June to October 2024, covering a study area of ​​21,881.41 ha. The method used is remote sensing, using Sentinel-2A satellite imagery, along with Geographic Information System (GIS) software, specifically ArcGIS, for mapping and spatial analysis. The NDVI classification results show five land cover categories based on NDVI value ranges. NDVI Class 1 (-0.38 to -0.02) includes non-vegetated land and water bodies. NDVI Class 2 (-0.02–0.20) indicates very low greenness, typically consisting of bare land. NDVI Class 3 (0.20–0.38) represents low greenness, which includes built-up areas. NDVI Class 4 (0.38–0.54) includes moderate greenness, typically found in plantations or fields, while NDVI Class 5 (0.54–0.83) represents high greenness, covering areas such as shrubs, forests, and mangroves. This analysis provides valuable information for land use planning and environmental management based on spatial vegetation data. The results of this study are expected to serve as a basis for policy-making that supports the sustainable management and conservation of vegetation in Langsa City.